2015
DOI: 10.1007/s11270-015-2600-6
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of Naphthenic Acids in Water: Kinetic Study

Abstract: The large amount of oil sands processaffected water (OSPW), produced from the extraction of oil from oil sands in Alberta, Canada, has demonstrated both acute and chronic toxicity to many species due to the presence of naphthenic acids (NAs). The Bzero discharge^policy posted by the Alberta government presents a major challenge for the oil sands industries. In this study, ozonation was used to remove model NAs from water. It was found that the removal of NAs increased with the temperature. The kinetics of dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Results of our previous studies confirmed that ozonation of NAs is carried out through two pathways: direct reaction of molecular ozone with NAs; and indirect oxidation of NAs by hydroxyl radicals formed from ozone self‐decomposition in water . The two pathways are as follows:…”
Section: Methodssupporting
confidence: 55%
See 4 more Smart Citations
“…Results of our previous studies confirmed that ozonation of NAs is carried out through two pathways: direct reaction of molecular ozone with NAs; and indirect oxidation of NAs by hydroxyl radicals formed from ozone self‐decomposition in water . The two pathways are as follows:…”
Section: Methodssupporting
confidence: 55%
“…The solutions were buffered with 5 × 10 −3 mol L −1 of sodium phosphate to maintain the pH at 8.5. More details were described previously . Table shows the experimental conditions applied in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations